Comparisons of Growth, Yield, and Meteorological Properties of Rice Canopy under Double-Row (Jajar Legowo and Jejer Manten) and Tile Transplanting Systems - Yuliawan, Taufiq; Ichwan, Nazif; Ukpoju, Augustine; Irsyad, Fadli; Oue, Hiroki (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Over the past decade, the Indonesian government has been recommending double-row transplanting systems, i.e., Jajar Legowo (JL) and Jejer Manten (JM), to increase rice production. These systems have been reported to obtain higher yield of Indica rice cultivars than the standard tile (TL) system, primarily due to the border effect. However, scientific investigations of the border effect in these transplanting systems remain limited. This study was conducted during the summer seasons in Japan in 2022 and 2023 to observe the plant growth and yield of a Japonica rice cultivar, Nikomaru, and to investigate differences in meteorological properties, such as intercepted solar radiation (SRint). The study found that higher plant competition for light in JM and JL caused a lower tiller number and above-ground biomass (Wt) per hill than in TL. However, due to denser planting, JM and JL obtained higher tiller numbers, Wt, and sink capacity per unit area than TL. Additionally, the denser canopy in JM and JL compared to TL increased SRint by the whole canopy, even though the space between the double rows was wider. Although SRint was not significantly different amongthe systems, higher normalized difference vegetation index in JM and JL was strongly correlated with a higher sink filling rate due to the healthier canopy absorbing more solar radiation. The synergistic effect of higher sink capacity and sink filling rate led to higher yields in JM and JL than in TL. This study suggests that JM is the best transplanting system for increasing rice yield.